(untitled) (PANGEEA, 2025)
Geological considerations on Metalogenetic District Zlatna-Stănija. Zlatna-Stănija metalogenetic district, located in the southern of Apuseni Mountains, is one of the most important mining regions in Romania. There have been exploited since ancient times, important deposits of gold and silver, being exploited in modern times and other metals (Pb, Zn, Cu). Ore from the mine shows a very complex chemistry and was processed at the ore factory in Zlatna. There have only been extracted Au, Ag, Pb, Zn, Cu and other metals (Mo, W, Te, Cr) remained in sterile material, which causes particular problems related to environmental pollution. Keywords: metalogenetic province, mining regions, complex ore, environmental pollution.